Situating tenure, capital and finance in farmland relations: implications for stewardship and agroecological health in Ontario, Canada. Issue 1 (2nd January 2019) - Rotz, Sarah; Fraser, Evan D.G.; Martin, Ralph C.
Abstract : Farmers in Canada are older and more capitalized than ever before. Meanwhile, farmland values continue to rise. These forces together are generating unprecedented shifts in farmland relations, marked by increasing reliance on rental tenure and the rise of hybrid owner–renter consolidating farmers. This paper explores these dynamics in Ontario and asks how they are impacting on-farm agroecological stewardship. To do so, we begin with a review of the land and property relations literature as well as farmland and agricultural change in Ontario. We then briefly review agroecological issues and concepts that are important for linking on-farm agroecological health to aformentioned farmland and agricultural changes. From here, we use survey, interview and soil sample data collected from grain farmers across Ontario to elucidate relatively new shifts in land tenure and use dynamics. We argue that this complex set of forces is interacting to produce an appealing set of conditions for financial investors, while restricting access to farmland for less-capitalized farmers. We then show how these shifts are divesting capital and attention from agroecological health. We conclude with a reflection on how the state has been mediating and contributing to these dynamics, and urgently call for land policy that prioritizes social and ecological principals.